A Feasibility Study On VoltKingTM DVM 1 - Estrada, Eric; Latonio, Patrick Gerald; Mangoba, Dianne Mayumi (Diliman, Quezon City College of Engineering, 2000)
The paper discusses the feasibility of VoltKing DVM-1, the first locally manufactured digital variable power supply. The product shall be known for its high density packing, digital window and keypad interface, and efficient power usage. The target market of Voltking DVM 1 will be Universities/Colleges that offer Electrical and Electronics Engineering Courses. There is a sufficiently large demand for Variable Power Supplies as compared to the supply. The projected demand and supply exhibited a very large gap. From the gap, a portion of the market will be captured by the product. The market share of the product is increasing throughout the five year study period, ranging from 2.1% on the first year, 4.1% for the second year, 6% for the fourth year, to 9.5% on the fifth year, 158 units on the second year, 247 units on the third year and 342 units on the third year and 342 units on the fourth year. The sales peak occurs on the fifth year, wherein 441 units of the product are expected to be sold. The DVM-1 shall be priced competitively at P14000 and shall be available nationwide. Advertising strategies for the product include distribution of brochures and product demonstrations to various schools around the country. Telephone assistance to product and service inquiries shall be conducted extensively. Long term warranties shall be granted to customers when they buy the product. The total marketing budget for the product is at its peak on the first year at P166700 due the product launching. Advertising strategies and the budget for these for the succeeding years become consistent, with the increase in budget solely attributed to inflation at 10% each year. Voltking DVM 1 has a future in the power supply business. Due to the lack of a strong presence from the Philippine Manufacturing Industry for quality power supplies, Voltking DVM 1 will overcome this inadequacy. Its many advantageous features will enable it to capture a significant part of the market, which is now being overrun by high priced, inefficient, inaccurate variable power supplies. Based on the information gathered ad analysis done, there is a sufficient market and demand for the product. It is therefore concluded that Voltking DVM 1 is feasible to introduce in the market. The company shall be located at #21 Scout Borromeo, Quezon City. This location was chosen primarily due to its proximity to the distributor and to other engineering schools offering ECE courses. The project is concluded to be technically feasible due to the following reasons: (1) the raw materials and equipment needed to produce the DVM 1 unit are locally available (either made here or made available by local distributors); (2) the technical skills required by the project is also locally available; and (3) the project cost yielded by the project is not that substantial, making it an attractive venture. Production of the power supply is increasing for the five year study period. The workforce includes a General manager, his secretary, a chief engineer, an accountant, a technical, a company driver and a janitor. The employees shall be subjected to 8 working hours a day for 5 days a week with no shifting in the schedule. The total space requirement for the plant is 74 sq. meters. The required space consists of the Production Area, an Office, a Warehouse, a Customer Waiting Area and Comfort Rooms. The project yielded a total project cost of P2,389,682.20 which is broken down into the fixed investment (P428,580.61), start-up cost (P157,238.69), working capital (P1,586,619.06) including a 10% contingency allowance (P217,243.84). Half of the project cost is financed through stockholders equity and the other half is financed through a loan from the Philippine National Bank. The business shall assume the corporation as its form of ownership due to the strong points it presents. As can be seen from the financial ratios, the company shows a stable financial position and a profitable position for the next five years. The ratios indicate that the company becomes more profitable and stable through the years. More of the company's assets become available for liquidation. Also, the company's ability to meet its debt requirements becomes greater through the five years of operation. From the break-even analysis, the company's sales volume, selling price, and sales are at a level above the minimum requirement to keep the company operational. The company's net present value for MARR 30% is greater than 0 and the internal rate of return (IRR) is greater than the MARR. This means that the project is an acceptable business venture. The payback period is 3.5 years. The Net Present Value for the business is P194,324.90. The Internal Rate of Return is 34.2% The project is therefore financially feasible since it shows commercial profitability and financial stability for the first five years of the project life. From the NPV and IRR, the business venture is acceptable. Also the payback period occurs within the 5 year study period. The business has numerous contributions to society. These include the contribution of taxes in the government, thus increasing its funds for community projects, the generation of employment, the creation of the product's availability in the local market, the none generation of harmful waste to the environment, the creation of a more competitive market which benefits end-users, and the transfer of technology to the country. The business is therefore deemed socially profitable.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Electric apparatus and appliances--Power supply--Direct current; Electric power systems--Equipment and supplies; Participatory monitoring and evaluation (Project management)